Identifying sources of variation in added sugar intake for Alaska Native children using a hair biomarker - Alice Ko; Diane O’Brien; Patricia Rivera; Lloyd Mancl; Scarlett Hopkins; Cameron Randall; Daisy Patiño Nguyen; Donald L. Chi (International Journal of Circumpolar Health, 2024)
Sugars from sugar-sweetened beverages (SSBs) are an important risk factor for tooth decay. The study goal was to determine if there was variation in added sugar intake across communities and between and within households. In this cross-sectional study, intakes of total sugar, added sugar, and sugar-sweetened beverages (SSBs) were estimated for 282 Alaska Native children ages 0–10 years from 131 households in three Yukon-Kuskokwim (YK) Delta communities using biomarker equations based on hair carbon and nitrogen isotope ratios previously developed for the Yup’ik population. ANOVA was used to assess associations between each predictor (community and household) and outcome (estimated total sugars, added sugars, and SSB intake). Between- and within-household variation was estimated using a linear mixed-effects model with a random intercept for households with three or more children. There was no significant difference in mean estimated total sugar (p = 0.29), added sugar (p = 0.24), or SSB intake (p = 0.40) across communities. Significant variations were observed between and within households, with within-household variation amounting to 59% of the between-household variation. Added sugar intake in Alaska Native children from the three study communities is higher than the recommended maximum, and the variation is greater within households than between households.